The Effect of Definitive Antibiotic Appropriateness on therapeutic Outcomes in Diabetic Ulcer Patients - Ulandari, Syaripah; Laksmi Meiliana, Made (Jurnal Kesehatan Cendikia Jenius, 2025)
Diabetic ulcers are infections, wounds, or tissue damage of the lower extremities in patients with diabetes mellitus caused by neuropathy and peripheral vascular impairment, which can lead to amputation. Up to 40% of amputation risks can be prevented through the use of appropriate antibiotic therapy. This study was to analyse the effect of the approproate use of definitive antibiotics on therapeutic outcomes in diabetic ulcer patients undergoing inpatient treatment at Hospital X in Bandar Lampung in 2023. used an analytical observational design with a retrospective cohort approach. The study population comprised 112 hospitalised patients diagnosed with diabetic ulcers, from which 87 patients were selected using the Slovin formula. Data were analysed descriptively to present patient characteristics, and the One-way ANOVA was used to examine the relationship between definitive antibiotic appropriateness and therapeutic outcomes. The results showed that 50 patients (57,5%) were female, the majority were aged 56-65 years (46%), and 80 patients(90%) received beta-lactam antibiotics. The One-way ANOVA test demonstrated a significant effects of appropriate definitive antibiotic use and improved therapeutic outcomes (p < 0.05). Improvements were observed in random blood glucose, HbA1c, leukocyte counts, and body temperature. Based on the result of this study, the appropriate use of definitive antibiotics can significantly improve the therapeutic outcome of diabetic ulcer patients. It is recommended that hospital pharmacies conduct intensive monitoring of antibiotic use to prevent futher infections that could lead to amputation and treatment resistance.